Update on the efficacy of the dermal apron technique: Increasing peri-implant mucosal thickness and tissue stability - Barry P. Levin (Elsevier, 2024)
Immediate tooth-replacement therapy can be a predictable method for treating anterior hopeless teeth. Preserving and augmenting both hard and soft tissues is critical for the physiologic and esthetic success of therapy. Utilizing a combined hard and soft tissue augmentation approach improves outcomes. Reducing morbidity associated with procuring autogenous grafts can be efficacious regarding short and long-term outcomes. The Dermal Apron Technique uses both bone and soft tissue allografts to increase soft tissue thickness around immediately placed and provisionalized implants. Studies demonstrate the increased soft tissue thickness produced by the technique. This article demonstrates the technique and discusses the clinical research supporting the use of this method for successful immediate tooth-replacement therapy.